Spatial variations and periodic changes in heavy metals in surface water and sediments of the Three Gorges Reservoir, China. (February 2020) - Lin, Li; Li, Chao; Yang, Wenjun; Zhao, Liangyuan; Liu, Min; Li, Qingyun; Crittenden, John C.
Abstract: Substantial changes have occurred in hydrological situation of the Three Gorges Reservoir (TGR) after the operation of the Three Gorges project, as have the heavy metals (HMs) pollution characteristics. In this study, concentrations of Cu, Zn, Pb, Cr, and Cd in surface water and sediments of the TGR were determined during the water impoundment period (December 2015) and water drawdown period (June 2016). The index of geoaccumulation, principal component analysis (PCA), and correlation analysis were used to analyze HMs pollution characteristics. Results showed that HMs concentrations in surface water were much lower than the quality standards for drinking water and surface water of China. The pollution levels of HMs in sediments were nonpolluted for Cr, nonpolluted to moderately polluted for Cu, Zn, Pb, and moderately polluted for Cd. In the fluctuating backflow zone, HMs concentrations in sediments during the water drawdown period were lower than those during the water impoundment period, which was attributed to that faster flow velocity during the water drawdown period resulted in less deposition of suspended solids and faster release of HMs pollutants from sediments to water. HMs concentrations of sediments at sites M14 and M17 showed similar periodic changes to those at the fluctuating backflow zone, which might be attributed to the density-stratified flow in the adjacent upstream tributaries (Meixi River and Qinggan River, respectively). Correlation analysis and PCA analysis results showed that for the sediments, Cr came from natural sources, while Cu, Zn, Pb, and Cd mainly came from anthropogenic sources. Graphical abstract: Image 1 Highlights: Spatial variations and periodic changes of HMs in TGR were systematically studied. HM concentrations in surface water fluctuated more intense spatially in the summer. HM concentrations in sediments in FBZ were lower in the water drawdown period. Periodic changes of HM concentrations in sediments varied depending on the site. Cr in sediments came from natural sources, while others from anthropogenic sources.